Time-lapse borehole radar measurements in a sandy groundwater system during a winter recharge cycle - Strobach, Elmar; Harris, Brett; Dupuis, Christian; Kepic, Anton; Martin, M. (IEEE Xplore, 2012)
Borehole Radar has demonstrated to be an effective method to determine water content profiles within the vadose zone. Time-lapse measurements shown in this study were acquired on the Gnangara Mound north of Perth, Western Australia. Borehole radar experiments using vertical radar profiling and zero-offset crosswell profiling acquisition geometries have been performed under different soil moisture conditions. Time-lapse repeatability proved robust for zero-offset profiles, while vertical radar profiles provided mixed results. The variations observed in the zero-offset profiling are expected to be related to the seasonal variations of soil moisture content since results from the saturated zone remained constant during the tests. We quantify the wetting front developing through the dry soil profile on a monthly basis. Infiltration behaviours are characterized under different scenarios ranging from homogeneous soil moisture distribution with shallow water tables to heterogeneous soil profiles including water retentive layers and the watertable at 12 m depth. The measured soil moisture profiles and infiltration observations have implications for groundwater recharge estimation and unsaturated flow parameter estimation.